Enhancing nurse faculty resilience through self-leadership: guidelines for resource mobilization in dynamic academic environments - Matahela, Vhothusa Edward; van Rensburg, Gisela Hildegard (Frontiers in Psychology, 2024)
The purpose of the study was to develop guidelines for the facilitation of self-leadership in nurse faculty. Of the 12 guidelines developed, this paper discusses the two related to resilience through self-leadership practices, namely: encouraging reliance on internal sources for self-preservation; and strengthening the positive self-image of nurse faculty through management and peer support. A sequential, exploratory-descriptive mixed-methods approach was used to guide the development of guidelines. Enhancing nurse faculty resilience can be achieved by promoting engagement in self-leadership activities. These activities contribute to faculty members' profound satisfaction, confidence in their knowledge, and overall competence. Resilience is enriched through practicing self-leadership in a supportive work environment and plays a crucial role in adapting to significant changes in the work environment. It has been identified as a key factor that facilitates the ability to persist against struggles and challenges in the workplace. The implementation of higher education reforms in South Africa has brought about increased workload, stress, and uncertainties to an already overwhelmed nurse faculty workforce, consisting of mainly female faculty. It is prudent that a supportive environment that empowers nurse faculty wellbeing and resilience be facilitated to ensure adaptation to a dynamic and competitive nursing education environment.